Students’ Speaking Proficiency and Self-efficacy Theory - Mohammed, Abdelaziz (Advances in Social Sciences Research Journal, 2021)
This study is aiming at investigating the possible source of Saudi EFL students' speaking self-efficacy that effect on their speaking proficiency. The investigation used Banduras' theory of self-efficacy as this theory has great effective factors and role in student’s ability in mastering any task. The study sample included 10 male and female students. Their proficiency was observed and analyzed collectively to find the real behaviors in real EFL classroom settings; and using Bandura's theory of self-efficacy in speaking component as appropriate criteria to study its expected source. The most important conclusion is that not only all the sources in Bandura's theory were found among Saudi EFL students, but also, they differ greatly according to each one’s proficiency experience and social persuasion. Additionally, it was found due to other factors as self-employed strategies and intellectual ability. Thus, the study recommended that it is important to warm-up students with advance activities to ease the positivity and overcome their negativity towards speaking skill. Finally, the study recommends conducting further research targeting a largest number of students for the purpose of studying speaking skill preferences in relation to other English language skills.